Diminished facial emotion expression and associated clinical characteristics in Anorexia Nervosa. (28th February 2016) - Lang, Katie; Larsson, Emma E.C.; Mavromara, Liza; Simic, Mima; Treasure, Janet; Tchanturia, Kate
Abstract: This study aimed to investigate emotion expression in a large group of children, adolescents and adults with Anorexia Nervosa (AN), and investigate the associated clinical correlates. One hundred and forty-one participants (AN=66, HC= 75) were recruited and positive and negative film clips were used to elicit emotion expressions. The Facial Activation Coding system (FACES) was used to code emotion expression. Subjective ratings of emotion were collected. Individuals with AN displayed less positive emotions during the positive film clip compared to healthy controls (HC). There was no significant difference between the groups on the Positive and Negative Affect Scale (PANAS). The AN group displayed emotional incongruence (reporting a different emotion to what would be expected given the stimuli, with limited facial affect to signal the emotion experienced), whereby they reported feeling significantly higher rates of negative emotion during the positive clip. There were no differences in emotion expression between the groups during the negative film clip. Despite this individuals with AN reported feeling significantly higher levels of negative emotions during the negative clip. Diminished positive emotion expression was associated with more severe clinical symptoms, which could suggest that these individuals represent a group with serious social difficulties, which may require specific attention in treatment. Highlights: Individuals with AN displayed altered emotion expression. They also displayed emotional incongruence. Reduced emotion expression was associated with worsening clinical characteristics. Reduced positive emotion expression may be indicative of poorer social functioning.